Human immunodeficiency virus type 1 transactivator protein, tat, stimulates transcriptional read-through of distal terminator sequences in vitro. - Graeble, M A (1993)
The human immunodeficiency virus type 1 transactivator protein, tat, specifically stimulates transcription from the viral long terminal repeat. We used cell-free transcription systems to test whether tat can stimulate transcriptional read-through of an artificial terminator sequence (e.g., a stable RNA stem-loop structure followed by a tract of nine uridine residues) placed downstream of the viral long terminal repeat. In the absence of tat, RNA polymerases are prematurely released from the template at the terminator sequence. Recombinant tat protein purified from Escherichia coli increased the synthesis of full-length transcripts approximately 25-fold and decreased the amount of transcripts ending at the terminator sequence. The reaction is strictly dependent upon the presence of a functional transactivation-responsive region (TAR) sequence. Mutations in the tat binding site on TAR RNA and mutations in the TAR RNA loop block transactivation in vivo. Neither type of mutation is able to respond to tat in vitro. These results strongly suggest that after transcription through the TAR region, tat modifies the transcription complex to increase its elongation capacity.